2019
DOI: 10.1186/s13049-019-0600-z
|View full text |Cite
|
Sign up to set email alerts
|

Unplanned out-of-hospital birth and risk factors of adverse perinatal outcome: findings from a prospective cohort

Abstract: Background In France, while most babies are delivered at hospital, emergency medical services (EMS) weekly manage calls for unplanned out-of-hospital births. The objective of our study was to describe neonatal morbidity and mortality, defined as death or neonatal intensive care unit hospitalization at Day 7, in a prospective multicentric cohort of unplanned out-of-hospital births. Methods We prospectively analyzed out-of-hospital births from 25 prehospital EMS units in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
2
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 21 publications
3
29
2
5
Order By: Relevance
“…1,12,20,21 Prematurity was most strongly associated with adverse infant outcomes of UOHDs, as found in earlier studies. 1,5,10,11,13 Birth during the most recent time period, 2008-2013, and delivery in areas with low population density were associated with an increased the risk of UOHDs but not with perinatal morbidity or mortality associated with UOHDs. Thus, this does not support the suspicion that such adverse events in UOHDs might be associated with increasing distances due to decreased numbers of delivery hospitals.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…1,12,20,21 Prematurity was most strongly associated with adverse infant outcomes of UOHDs, as found in earlier studies. 1,5,10,11,13 Birth during the most recent time period, 2008-2013, and delivery in areas with low population density were associated with an increased the risk of UOHDs but not with perinatal morbidity or mortality associated with UOHDs. Thus, this does not support the suspicion that such adverse events in UOHDs might be associated with increasing distances due to decreased numbers of delivery hospitals.…”
Section: Discussionmentioning
confidence: 92%
“…1,5,[9][10][11] We assessed risk factors associated with UOHDs in our earlier work and showed that risk factors associated with UOHDs were smoking during pregnancy, short labor, higher number of previous deliveries, single status, a distance from home to the delivery unit of more than 35 km and fewer prenatal visits. 12 One previous study, revealing risk factors for adverse neonatal outcome, 13 found that multiparity, prematurity, maternal pathology and neonatal hypothermia were independent risk factors of neonatal mortality and morbidity.…”
Section: Introductionmentioning
confidence: 95%
“…They were most often planned to take place with assistance ("planned delivery") and only 0.1% took place without any assistance [8]. When a mobile emergency service was called, the medical team delivered the newborn in a third of cases [9].…”
Section: Introductionmentioning
confidence: 99%
“…Out-of-hospital delivery is associated with unfavorable perinatal outcomes and increased mortality [2,5,6], with hypothermia being the most frequently described adverse outcome [1,7,8]. Indeed, hypothermia is recognized as a significant risk factor for mortality under these conditions [9,10]. In low birth weight infants, mortality increases by 28% per 1°C decrease of body temperature from birth to admission in the neonatal intensive care unit [11].…”
Section: Introductionmentioning
confidence: 99%